2017
DOI: 10.1016/j.gaitpost.2017.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Functional implications of muscle co-contraction during gait in advanced age

Abstract: Older adults often exhibit high levels of lower extremity muscle co-contraction, which may be the cause or effect of age-related impairments in gait and associated falls. Normal gait requires intact executive function and thus can be slowed by challenging executive resources available to the neuromuscular system through the performance of a dual task. We therefore investigated associations between lower limb co-contraction and gait characteristics under normal and dual task conditions in healthy older adults (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 26 publications
1
30
1
Order By: Relevance
“…Muscle co-contraction was defined as the common activity presented as a percentage of total muscle activity in a pair of antagonist muscles within a gait cycle 19 . Figure 2 showed the schematic of lower limb muscle co-contraction.…”
Section: Experimental Set-upmentioning
confidence: 99%
“…Muscle co-contraction was defined as the common activity presented as a percentage of total muscle activity in a pair of antagonist muscles within a gait cycle 19 . Figure 2 showed the schematic of lower limb muscle co-contraction.…”
Section: Experimental Set-upmentioning
confidence: 99%
“…The magnitude of differences observed in muscle co-contractions might appear to be relatively small. However, previous research by Lo and colleagues [24] demonstrated that even seemingly trivial increases in co-contraction are significantly associated with increased swing and stance durations. The clinical importance of increased co-contraction not only relates to consequential alterations in gait characteristics, but also to increased risk of falls by increasing lower limb rigidity/stiffness which impedes reactive adaptation to postural perturbations [22,25].…”
Section: Discussionmentioning
confidence: 95%
“…While existing literature suggests that even a small change (<5% change in co-contractions observed in Lo et al . [24]) might be necessary to induce significant behavioural changes and influence movement efficiency, future work should endeavour to identify such thresholds so that clinicians might avail of such measures when evaluating neuromuscular efficiency in patients.…”
Section: Discussionmentioning
confidence: 99%
“…By regression analysis this study further examined the relationship between the magnitude and frequency parameters of multiple muscles and knee flexion in post-stroke gait ( Table 2 ). Although a few studies have established associations between lower-limb muscles’ coordination patterns and knee joint kinematics for healthy individuals [ 26 , 27 ], less is known about how the stroke interferes with these associations during the stance-to-swing phases of the gait cycle. The changes in muscles’ activation patterns and muscle coordination during walking has been considered to give rise to the decreased knee angles [ 5 ].…”
Section: Discussionmentioning
confidence: 99%